Manajemen Pembelajaran Fiqih Dengan Media Youtube Untuk Meningkatkan Minat Belajar Siswa - Oktaviani, Amanda Eka; Istikomah, Istikomah (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2023)
Teaching and learning activities in the current digital era must master internet technology with various platforms including fiqh learning. Fiqh learning is a compulsory subject for all levels of education. In the management of fiqh learning, educators are required to have the ability to modify the learning process, therefore, fiqh learning material will be liked and find it interesting for students. The purpose of this study is to describe the management of fiqh learning with YouTube media. This research is a type of qualitative research with a case study approach. Data collection techniques were carried out by means of interviews, observations, and documentation in this research. It states that the management of learning fiqh at MI Roudlotul Ulum is carried out in accordance with the learning mechanism and based on the desired learning objectives. The achievement of good learning outcomes depends on the ability of educators to manage learning.